EFFECT OF ONGOING TREATMENT AND DIFFERENT THERAPIES ON PROGNOSIS IN COVID-19 PATIENTS IN AN HOSPITAL SETTING. (April 2021) - Bianco, Gianluca; Boari, Gianluca E.M.; Bonetti, Silvia; Chiarini, Giulia; Orlandini, Federico Braglia; Faustini, Cristina; Malerba, Paolo; Rizzoni, Damiano
Abstract : Objective: Patients affected by novel pandemic SARS-CoV-2 may develop COVID-19 related pneumonia, which is potentially fatal. To date, the role of ongoing treatments for different conditions (such as hypertension) has been clarified in terms of their impact on survival and there is no established specific therapy for the disease, although many molecules are under investigation. Aim of the present study was testing those two issues in a population of 258 consecutive patients admitted from 29 February to 30 April 2020 to General Medicine ward of the Hospital of Montichiari (Brixia). Design and method: A group of 258 patients (173 males and 85 females, aged 71 ± 14) was enrolled. Their medical record and ongoing treatment were assessed. Patients were treated according to emerging information with oxygen, anti-malarian agents, anti-viral drugs, different antibiotics (azithromycin and others), tocilizumab and low molecular weight heparin (LMWH) at different doses. As of June 10th, 65 deaths had been observed. Survival curves were calculated according to Kaplan-Meier method. Comparison between groups was performed with Breslow and Mantel-Cox test Results: Ongoing therapy with ACE-inhibitors at the time of admission was associated with a worse prognosis (p = 0.004), while no difference in survival was observed in patients under treatment with ARBs (p = 0.68). Ongoing treatment with statins (p < 0.001), low-dose aspirin (p < 0.001) and steroids (p < 0.001) was associated with a poorer outcome as well Administration during hospitalization of LMWH (p < 0.001), steroids (p < 0.001), anti-viral drugs (p = 0.002), anti-malarian drugs (p < 0.001) and tocilizumab (p < 0.001), improved prognosis, while antibiotics (azithromycin and other) didn't have any impact. Figure. No caption available. Conclusions: our experience confirms most findings in ongoing trials. Surprisingly, treatment with ACE-inhibitors seems to impact negatively on survival in patients affected by SARS-CoV-2 pneumonia. A possible explanation may be that patients treated with certain drugs are more comorbid and due to this, more fragile.